HIGH-RESOLUTION INFRARED-SPECTROSCOPY OF THE CO.CO2 VANDERWAALS MOLECULE - Randall, R; Summersgill, J; Howard, B (1990)
We report the infrared absorption spectrum of the CO·CO2 van der Waals molecule in the region of the CO fundamental stretching vibration. By simultaneously fitting the observed spectrum with the previously observed microwave spectrum we have determined the upper-state spectroscopic constants. These are given as νo = 2148.241 44(14) cm-1, Δνo = 4.970 28(14) cm-1, A′ = 11 869.4(1.6) MHz, B′ = 1874.68(40) MHz and C′ = 1608.77(24) MHz. Using a model including electrostatic multipole and dispersion interactions we have constructed potentials for various structures. The experimentally observed structure is found to be the more stable.